PERSEPSI TENTANG SEKSUALITAS SESUAI JENIS KELAMIN PADA SISWA SMK LPI SEMARANG: Persepsi Tentang Seksualitas Sesuai Jenis Kelamin - Novia Heldiana; Yovitha Yuliejantiningsih (Dharmas Education Journal (DE_Journal), 2021)
This research is based on the increasing number of cases of free sex in adolescents, especially high school and vocational high school students. Boys and girls in their sexuality respond differently. The difference between students in the causes of sexuality is what drives them to provide sexuality education in schools. The main problem being studied is whether there is a difference in the perception of sexuality according to gender among students of SMK LPI Semarang? The purpose of this research is to determine the perception of sexuality perceptions according to gender in SMK LPI Semarang students which will be used as evaluation material for BK teachers in order to provide sexuality education to students of SMK LPI Semarang. This research method was quantitative ex post facto. The population in this study were all students of SMK LPI Semarang consisting of class X, XI, and XII which can be said to be 142 students. The sample used consisted of 41 male students and 51 female students. The technique used was Proportional Random Sampling. The data were collected using a psychological scale of sexuality perception. The results show the fact that the perception of perceptions in the male group with the female group. Based on the calculation of the analysis of research conducted by researchers at SMK LPI Semarang, the results so that a T-count value is 0.516. This can answer the hypothesis by comparing the T-count, with the T-table, namely 0.516 < 0.607 so that Hₒ is rejected, which means that there is a difference in perception between the male group and the female group.